Enactive appropriation. Issue 1 (February 2016) - Flint, Tom; Turner, Phil
Abstract The appropriation of digital artefacts involves their use, which has changed, evolved or developed beyond their original design. Thus, to understand appropriation, we must understand use. We define use as the active, purposive exploitation of the affordances offered by the technology and from this perspective; appropriation emerges as a natural consequence of this enactive use. Enaction tells us that perception is an active process. It is something we do, and not something that happens to us. From this reading, use then becomes the active exploitation of the affordances offered us by the artefact, system or service. In turn, we define appropriation as the engagement with these actively disclosed affordances—disclosed as a consequence of, not just, seeing but ofseeing as . We present a small case study that highlights instances of perception as an actively engaged skill. We conclude that appropriation is a simple consequence of enactive perception.